Correction: LudusScope: Accessible Interactive Smartphone Microscopy for Life-Science Education. - Honesty Kim; Lukas Cyrill Gerber; Daniel Chiu; Seung Ah Lee; Nate J Cira; Sherwin Yuyang Xia; Ingmar H Riedel-Kruse (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0162602.].